Even in a global pandemic, there's no such thing as a crisis. (June 2020) - Spector, Bert
In my 2019 publication, Constructing Crisis: Leaders, Crisis, and Claims of Urgency, I argued that "crisis" is a label, a claim of urgency employed, typically by leaders, to characterize a set of contingencies that are, together, taken to pose a serious and immediate threat. I then proposed a typology for sorting through any such claim in order to reach a judgment concerning the legitimacy of the claim. Classification systems such as typologies are foundational to knowledge creation in that they enable pattern recognition.. How we classify phenomenon has a real impact on how we consider and behave in response to that phenomenon. In the context of a global pandemic, the importance of critical judgment is especially salient. Labeling the global pandemic as a crisis may be non-controversial (to most). But there are enumerable claims being made under the general rubric of that pandemic that are not nearly so widely and easily accepted. Furthermore, claims of urgency will continue long after this particular contingency passes. It is never advisable to relax a critical perspective, especially when assertions of power and interests are involved and the stakes are so high.